Metallic conductivity of the heterointerface between LaFeO3 and SrTiO3. (January 2021) - Nishikawa, Hiroaki; Itani, Fumiya; Kawaguchi, Tadao; Tanaka, Hidekazu; Iwata, Nobuyuki
Abstract: Carrier doping to 3 d transition metal oxides was proposed as an effective 3 d band-filling control method. The mechanism differs from that previously reported to involve "charge discontinuity at the heterointerface". The mechanism uses the energy difference between 3 d bands beyond the heterointerface, with the relative energy of the O2 p band being shared at the heterointerface. To test the proposal, electrical conductivity was investigated at the heterointerface between LaFeO3 and SrTiO3 . The LaFeO3 /SrTiO3 heterointerface showed a metallic conductivity similar to that observed for a LaAlO3 /SrTiO3 heterointerface. However, the sheet resistance of the LaFeO3 /SrTiO3 system was larger than that of the previously reported LaAlO3 /SrTiO3 system. The dependence of the sheet conductance on the thickness of the LaFeO3 layer also differed from the corresponding dependence of the LaAlO3 /SrTiO3 system. These findings suggest it is possible to control the Fe3 d 6 band-filling of LaFeO3 by retransfer of electrons from the TiO2 layer to the FeO2 layer. Highlights: LaFeO3 (LFO)/SrTiO3 (STO) system displayed a metallic conductivity. The metallic conductivity occurs at the LFO/STO heterointerface. The sheet resistance of the LFO/STO was larger than that of the LaAlO3 /STO. It is possible to control the filling of the Fe3 d 6 band of LFO. The filling mechanism used the energy difference between Fe3 d 6 and Ti3 d 1 .